Save me - Scottoline, Lisa. (New York : St. Martin's Press, 2011)
When an explosion rips through the nearly empty cafeteria mother Rose McKenna leads two girls to safety and rescues her own daughter. But Rose soon learns that she may face both civil and criminal charges for her heroics.
Keywords: Explosions -- Fiction; Mothers and daughters -- Fiction; Bullying in schools -- Fiction; Motherhood -- Fiction; Domestic fiction